PERANCANGAN SISTEM APLIKASI CARING BY ME BAGI PENUMPANG DISABILITAS PESAWAT UDARA BERBASIS IOT - Vrilo Rahmadani Tantowi; Ariyono Setiawan; Wiwid Suryono (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The commitment of an airport is to provide the best services and facilities for all passengers of air transportation modes, including persons with disabilities. Article 29 paragraph (1) of Law Number 25 of 2009 states that the organizer has the responsibility to provide services and facilities with special treatment to certain community members in accordance with the provisions of the legislation. In this case, certain communities, one of which is passengers with disabilities. This journal describes the design of an internet of things-based application system called caring by me. Caring by me is a public service platform for passengers with disabilities using air transportation, with this platform passengers with disabilities can report the need or difficulties experienced to travel using air transportation. This platform can be integrated with the service division of every airline operating at Indonesian airports and this can be used by passengers with disabilities to get various services and facilities such as special assistants, wheelchairs, canes or special requests such as health service translators and will continue to grow as time goes by. time. This design was carried out with Research and Development (R&D) research, with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model development procedure.